Comparative Gamification Practices for Information Literacy Instruction in Higher Education - Nikki Squire (Journal of Scholarly Engagement)
Due to the recent call for the need to change information literacy instruction for 21st century skills, many scholars, educators, and librarians are exploring gamification as a teaching and learning pedagogy for information literacy instruction, design, and assessment for student learning. The research literature provides an overview of various information literacy tools, teaching methods, and pedagogies suggested by scholars and educators for improving information literacy instruction and student learning. Based on results from empirical studies, to improve information literacy outcomes for undergraduate students, especially literacy gains for at-risk or underperforming students, gamification can be used as a conceptual framework for pedagogy assessment for teaching and learning.